Fortifikasi tepung kulit pisang (Musa paradisiaca) sebagai alternatif penambah nilai gizi dan daya terima nugget ayam - Cahyaning Rini Utami (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
The high fiber content in banana peels means that banana peel waste can still be used for processed food. One of the innovations in food processing involves fortifying banana peels in making nuggets. Generally, nuggets are made from chicken meat and filled with wheat flour. The research aimed to analyze the effect of adding banana peel flour and chicken meat concentration on the chemical and organoleptic characteristics of the nuggets and to determine the appropriate treatment to get the best banana peel-fortified chicken nuggets. The method used in the research was a Randomized Block Design (RBD) with 2 factors, namely banana peel flour (4%, 6%, 8%) and chicken meat concentration (40%, 80%), tested in 18 experiments. The chemical analysis carried out includes fiber, protein, and water content, as well as organoleptic tests (taste, aroma, texture, color). The study found that the combination of banana peel flour and chicken meat significantly affected taste and aroma, but not color and texture. The best treatment was P1D2 (4% banana peel flour, 80% chicken meat) with a fiber content of 3.12%, protein 13.14%, water 50.80%, and taste hedonic score of 4.23, aroma 3.77, texture 3.57, and color 3.40.